Accreditation Policies Implementation to Improve Performance Quality in Madrasah - Taufik Rahman; Iim Wasliman; King Muttaqien; R. Supyan Sauri (INTERNATIONAL JOURNAL OF EDUCATIONAL REVIEW, 2021)
Accreditation policy is based on the principle that all citizens have the right to obtain a quality education. In order to hold quality education, every educational program should fulfill the standard of accreditation policies Madrasah Tsanawiyah Negeri. Hence, this research aimed (1) to investigate MTsN accreditation policy, (2) to investigate the implementation of MTsN accreditation policy, (3) to examine the monitoring and evaluation of MTsN accreditation policy, and (4) to examine creative and innovative ideas of the implementation of MTsN accreditation policy. This research employed a qualitative approach with a Case Study method. The results were (1) The MTsN accreditation policy had been formulated in the vision, mission, and objectives of Madrasah, (2) the implementation of MTsN accreditation policy faced a problem of facilities and teachers’ skill in preparing educational administration documents, (3) monitoring and evaluation of MTsN accreditation policy was based on Madrasah Self-Evaluation (EDM), (4) creative and innovative ideas in the implementation of MTsN accreditation policy was based on Madrasah Self-Evaluation (EDM) conducted by the Madrasah Principle and teachers, Madrasah committee, parents, as well as a supervisor.